Physico-chemical properties of water and soil of Bhimsen Pokhari Wetland, Jhapa District, Eastern Nepal - Bhattarai, Krishna Prasad; Shrestha, Prem Kumar; Koirala, Omkanta (Nepalese Journal of Biosciences, 2017)
The functioning of an aquatic ecosystem and its stability support life forms, depend to a great extent on the physico-chemical characteristics of its water and soil. Physico- chemical properties of water and soil were determined in Bhimsen Pokhari wetland of Jhapa districts, eastern Nepal. Soil samples were collected from six sampling sites and analyzed triplicate for each samples. In all sampling site had sandy loam type of soil texture. The proportion of sand showed a marked increase from middle part to corner but clay decrease from middle to corner of the wetland. The acidic nature of soil increased from corner to middle part of the wetland. Soil organic carbon of wetland was higher in the middle part (2.31%) and lower in the North-west corner (1.72%). The result of water analysis showed that the middle part of wetland was slightly acidic than other sampling sites. From the same sampling sites the dissolved oxygen (5.81 mg L-1), total hardness of water (36 ppm) were found higher than other sampling sites. Dissolved oxygen was negatively correlated with the water temperature and pH but positive correlation with the total hardness of water. In conclusion, the middle part of the wetland may be the suitable site for the growth and development of aquatic flora and fauna as well as microbial activities due to having the higher amount of dissolved oxygen and soil organic matter.